"It's personalized, but it's still bucket based": the promise of personalized medicine vs. the reality of genomic risk stratification in a breast cancer screening trial. Issue 3 (3rd July 2022) - James, Jennifer Elyse; Joseph, Galen
Abstract : Adaptive pragmatic clinical trials offer an innovative approach that integrates clinical care and research. Yet, blurring the boundaries between research and clinical care raises questions about how clinicians and investigators balance their patient care and research roles and what types of knowledge and risk assessment are most valued. This paper presents findings from an ethnographic ELSI (Ethical, Legal, Social Implications) study of an innovative clinical trial of risk-based breast cancer screening that utilizes genomics to stratify risk and recommend a breast cancer screening schedule commensurate with the assessed risk. We argue that the trial demonstrates a fundamental tension between the promissory ideals of personalized medicine, and the reality of implementing risk-stratified care on a population scale. We examine the development of a Screening Assignment Review Board in response to this tension which allows clinician-investigators to negotiate, but never fully resolve, the inherent contradiction of "precision population screening."